Developing global champions: Why national oil companies expand abroad. (30th May 2019) - Cheon, Andrew
Abstract: National oil companies (NOCs) have invested hundreds of billions of dollars in foreign oil and gas assets. Why have some governments increased their NOC outward investments, while others have not? I argue that domestic structures can influence a government's calculus that potential benefits, such as added revenues and fuel supply, outweigh potential costs, such as information asymmetries and inefficiencies associated with NOCs. Nationally, partisan competition limits democratic tolerance for failures by NOCs. Bureaucratically, overlapping authority in energy policy undermines coherent NOC governance. Based on investments by NOCs hailing from 79 countries, 2000–2013, I find robust evidence for the national hypothesis.